2003
DOI: 10.3168/jds.s0022-0302(03)73729-1
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Lactoferrin Improves Health and Growth of Holstein Calves during the Preweaning Phase

Abstract: Lactoferrin is a milk protein that exhibits broad-spectrum antimicrobial properties. Previous studies indicated that supplemental lactoferrin may alter the microbial populations in the gut of nonruminants and increase preweaning weight gains in calves. In the present study, 40 Holstein calves were used to examine the effects of supplemental lactoferrin (0, 1, 2, or 3 g/d) on health, growth, and feed intake from 3 d of age to 2 wk postweaning. Lactoferrin was mixed and fed with a nonmedicated milk replacer. Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
4
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 17 publications
(21 reference statements)
2
44
4
3
Order By: Relevance
“…(Humphrey et al 2002;Robblee et al 2003). Here, the mean cumulative weight gain for animals fed HLZ milk was significantly higher during weeks 3-5 of the trial (Fig.…”
Section: Materials Results and Discussionmentioning
confidence: 74%
“…(Humphrey et al 2002;Robblee et al 2003). Here, the mean cumulative weight gain for animals fed HLZ milk was significantly higher during weeks 3-5 of the trial (Fig.…”
Section: Materials Results and Discussionmentioning
confidence: 74%
“…Regarding iron metabolism, Fe-bLF administration increased hemoglobin and red blood cells in iron-deficient anemic rats (Kawakami, Hiratsuka, & Dosako, 1988), whereas administration of Fe-bLF at high dose decreased hepatic iron content in weaning mice fed excess iron (Hagiwara et al, 1997). It is reported that oral LF reduces fat content in the serum and liver in mice , vascular endothelial growth factor A (VEGF-A)-mediated angiogenesis in rats (Norrby, 2004), and weight gain in preweaning calves (Robblee et al, 2003).…”
Section: Article In Pressmentioning
confidence: 96%
“…Lf has been reported to have important nutraceutical and biological properties such as antimicrobial activities [6] and regulating the immune system [7]. It is known to act as a growth factor by stimulating mucosal growth of the small intestine [8] and to increase hepatic protein synthesis in newborn [9]. It modulates the inflammatory response [10].…”
Section: Introductionmentioning
confidence: 99%